The Role of Student Entrepreneurial Capital in Advancing Islamic Entrepreneurship Development - Sugiarto S; Alawiyah Hasanah; Astin Eka Afrianti; Shafiyyah S; Isyqi Fadhlilhaq; Ztifania Dewi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the role of student business capital in the development of Islamic entrepreneurship. Business capital is understood not only as financial capital but also includes non-financial capital such as knowledge, skills, social networks, and an understanding of Islamic values. This research employs a qualitative descriptive approach using a literature review method by examining various sources, including books, scientific journals, and relevant documents related to Islamic entrepreneurship and student business capital. The findings indicate that business capital plays a significant role in encouraging students’ motivation to start a business, determining the type and scale of enterprises, and supporting business sustainability and growth. From the perspective of Islamic entrepreneurship, capital obtained from halal sources and managed with trustworthiness contributes to business sustainability and social welfare. Furthermore, campus environmental support, access to Islamic financial institutions, and strong social capital strengthen the role of business capital in fostering Islamic entrepreneurship among students. This study is expected to serve as a reference for higher education institutions and policymakers in developing student entrepreneurship programs based on Islamic values.